2018
DOI: 10.1021/acs.jpcb.8b03839
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mobility Effect on Magnetic Interactions in All-Organic Paramagnetic Liquid Crystal with Nitroxide Radical as a Hydrogen-Bonding Acceptor

Abstract: We synthesized new chiral all-organic liquid crystalline (LC) compounds with nitroxide (NO) and hydroxy (OH) groups, which form intermolecular hydrogen bonds between the NO and OH groups. The LC compounds show hexagonal columnar phases at room temperature, which solidify as LC glasses at low temperature. The experimental magnetic susceptibility of each of the compounds in the LC and isotropic phases is larger than that theoretically estimated on the simple assumption about the amount of the spins, whereas it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…With this situation in mind, since 2004, we have designed and synthesized a series of chiral and achiral all-organic LC nitroxide radicals such as 1-5 having one or two PROXYL (2,2,5,5-tetrassubstituted-1-pyrrolidinyloxyl) units in the core position and, thereby, with a negative dielectric anisotropy (∆ε < 0) ( Figure 3) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Their LC phases and magnetic properties have been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With this situation in mind, since 2004, we have designed and synthesized a series of chiral and achiral all-organic LC nitroxide radicals such as 1-5 having one or two PROXYL (2,2,5,5-tetrassubstituted-1-pyrrolidinyloxyl) units in the core position and, thereby, with a negative dielectric anisotropy (∆ε < 0) ( Figure 3) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Their LC phases and magnetic properties have been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, quite recently, by means of molecular dynamic (MD) simulation and density functional theory (DFT) calculations, Uchida et al has revealed that the positive magneto-LC effect can originate from the conservation of the memory of spin-spin interactions between magnetic moments, owing to the ceaseless molecular contacts in the LC and isotropic states. They incorporated the molecular mobility effects [44] into the quantitative Thouless-Anderson-Palmer approach, which was proposed to solve the Edwards-Anderson model for spin-glasses with inhomogeneous magnetic interactions [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an urgent topic in the development of future functional radical materials is the creation of molecules with spin properties that can be significantly controlled upon brief and weak external stimuli based on domino-type sequential changes 10 in molecular arrangements. However, such a sophisticated spin control and the necessary rational molecular designs have long remained undiscovered, likely due to difficulties in achieving π-conjugated radicals with sufficient molecular mobility, 11 as they definitively require molecular rigidity in their structures. This dilemma has inspired the development of new methodologies employing molecular fluidity in the radical associates under neat conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the optical switching owing to the molecular reorientation in a magnetic field [22] has some advantages in remote operability [8]. However, to reorient the nematic director using a weak magnetic field, high magnetic anisotropy ∆ χ of the LC molecule is needed [23,24], which is defined as the subtraction of the molar magnetic susceptibility component ( χ ⊥ ) perpendicular to the molecular long axis from that ( χ ) parallel to the axis [25].…”
Section: Introductionmentioning
confidence: 99%